nLCA in bakery food products: state of the art and urgent needs - Cassarino, Martina; Giuberti, Gianluca; Morelli, Lorenzo; Trezzi, Marco; Pelattieri, Andrea; Manicardi, Loris; Scaglia, Pietro (Frontiers in Sustainable Food Systems, 2024)
This study analyzes the nutritional life cycle assessment (LCA) of bakery products and the current state of the art. The analysis focuses on (1) the importance of applying a methodology, such as LCA, in a general way and the division into different stages considering the UNI EN ISO; (2) the development of nutritional LCA; (3) the difference between functional units in LCA and nutritional LCA; and (4) the different nutritional LCA approaches. The study emphasizes the lack of nutritional LCA studies regarding the bakery category, underlining the urgent need for this type of investigation concerning this specific food sector.